The impact of picture and picture learning model on EFL students’ writing ability - Rusmiati, Rusmiati; Miko, Mahara; Shaumiwaty, Shaumiwaty (Accentia: Journal of English Language and Education, 2023)
Writing has been a very challenging skill for students especially for eight grade learners of one Islamic junior high school in Central Aceh. This research was conducted to see whether the picture and picture-learning model could increase the students’ capability in writing. To investigate it, the quantitative approach, i.e., experimental method was employed. The population of this study was four classes, totaling 124 students. By using random sampling, classes VIII1 and VIII3 consisting of 30 and 32 students, respectively, were selected as the sample of this research. To collect the data, both pretest and posttest were given to the students before and after applying the picture-learning model. The results showed that the learners performed better after the intervention for both groups; however, the experimental group made better improvement in their writing (post-test = 84; pre-test = 60). In addition, the t-test also displayed that t-test (3.603) was higher than t-table (3.0) indicating that Ha was accepted and Ho was rejected. The conclusion, therefore, was that the picture and picture-learning model increased the students’ writing ability.